Epidemiological characteristics of SHV, cmlv, and FosA6-producing carbapenem-resistant Klebsiella pneumoniae based on whole genome sequences in Jiangsu, China - Zhu, Jiaying; Ju, Yanmin; Zhou, Xinyu; Chen, Taoyu; Zhuge, Xiangkai; Dai, Jianjun (Frontiers in Microbiology, 2023)
Carbapenem-resistant Klebsiella pneumoniae (CRKP), particularly those with high virulence, cause invasive disease in clinical settings. An epidemiological investigation was conducted on the evolution, virulence, and antimicrobial resistance of CRKP isolates in two tertiary teaching hospitals in Jiangsu, China from November 2020 to December 2021. There were 31 different CRKP strains discovered. We performed whole genome sequencing (WGS) on 13 SHV, cmlv, and FosA6-producing CRKP to reveal molecular characteristics. Five ST15/ST11 isolates had CRISPR-Cas systems. By conjugation tests, KPC-2 can be transmitted horizontally to E.coil. A conjugative pHN7A8-related multi-resistance plasmid (KPC-2, CTX-M-65, blaTEM-1, fosA3, catII, and rmtB) was first discovered in CRKP clinical isolates. Using bacteriological testing, a serum killing assay, and an infection model with Galleria mellonella, three ST11-K64 KPC-2 generating carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) were identified. These strains harboured a virulent plasmid and an IncFII-family pKPC/pHN7A8 conjugative plasmid, which led to hypervirulence and resistance. One of these CR-hvKPs, which co-harbored KPC-2, NDM-6, SHV-182, SHV-64, and blaCTX-M-122 genes, was first discovered. Importantly, this CR-hvKP strain also produced biofilm and had non-inferior fitness. The widespread use of ceftazidime/avibactam might provide this CR-hvKP with a selective advantage; hence, immediate action is required to stop its dissemination. Another important finding is the novel ST6136 in K. pneumoniae. Finally, the sterilization efficiency rates of Fe2C nanoparticles in CRKP were more than 98%. Furthermore, our novel antibacterial Fe2C nanoparticles may also provide a therapeutic strategy for infections.